The character and distribution of physical contaminants found in soil previously treated with mixed waste organic outputs and garden waste compost. (1st January 2020) - Cattle, Stephen R.; Robinson, Carl; Whatmuff, Mark
Highlights: Application of municipal solid waste compost to land coarsens the topsoil. Plastic and glass contaminants envelop and nucleate soil mineral grains. Microplastics block pore space in the soil, threatening water percolation. Abstract: The re-use of waste materials by application to land is an increasingly common practice around the world, but where municipal solid waste materials are applied, it is almost inevitable that physical contaminants such as glass and plastic will be added to the soil. In many jurisdictions, there are prescribed limits for the amounts of physical contaminants that may be present in these materials, but there is little information on whether these limits safeguard soil functional condition. Here, physical contamination of soil is described after varying rates of a mixed waste organic output (MWOO) and garden waste compost (GWC) were incorporated into field plots. At application rates of 100 and 200 t/ha, both treatments resulted in a coarsening of the topsoil particle size distribution, but only in the MWOO-treated soils were physical contaminants largely responsible for this. The physical contaminant particles present were found only to the depth of cultivation, and included glass, rigid and film plastics, and synthetic fibres. These contaminants were most commonly observed in the gravel and coarse sand-sized fractions, and in those soils treated with the highest rates of MWOO application. Physical contaminant particles acted as both enveloping and nucleating agents for mineral grains and organic matter, and blocked some pores. Although soil physical condition is usually improved by the incorporation of organic matter, the extent of pore blockage evident here suggests that soil physical functions such as water percolation may be affected as the organic matter is broken down and the soil undergoes natural re-consolidation.